Computational nanotechnology using finite difference time domain - Musa, Sarhan M. (CRC Press, Taylor & Francis Group, 2014)
"Written in a manner that is easily digestible to beginners and useful to seasoned professionals, this book introduces the key concepts of computational Finite Difference Time Domain (FDTD) method used in nanotechnology. It covers future applications of nanotechnology in technical industry as well as new developments and interdisciplinary research in engineering, science, and medicine. It includes an overview of computational nanotechnologies using FDTD method and describes the technologies with an emphasis on how they work and their key benefits. "--Resumé vydavatele
Keywords: nanotechnologie; nanofotonika; zpracování dat; numerické metody; modelování a simulace; nanotechnology; nanophotonics; data processing; numerical methods; modeling and simulation; metoda konečných diferencí v časové oblasti -- FDTD; sborníky; papers of several authors